2008
DOI: 10.1200/jco.2007.14.8841
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Severe Late Toxicity After Concurrent Chemoradiation for Locally Advanced Head and Neck Cancer: An RTOG Analysis

Abstract: Severe late toxicity after CCRT is common. Older age, advanced T-stage, and larynx/hypopharynx primary site were strong independent risk factors. Neck dissection after CCRT was associated with an increased risk of these complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
716
6
18

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 1,236 publications
(762 citation statements)
references
References 33 publications
22
716
6
18
Order By: Relevance
“…Although baseline characteristics appear reasonably matched, it is not possible to exclude biases which may have influenced the choice of feeding route which may also influence long term swallowing function. The study group was heterogenous with regard to radiation doses and the number of cycles of concurrent chemotherapy administered; both of these factors are recognised to impact upon swallow function 7,16 . For example, the slightly lower mean BMI in the prophylactic gastrostomy group may reflect a tendancy to choose this approach in patients who may be nutritionally compromised pre-treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although baseline characteristics appear reasonably matched, it is not possible to exclude biases which may have influenced the choice of feeding route which may also influence long term swallowing function. The study group was heterogenous with regard to radiation doses and the number of cycles of concurrent chemotherapy administered; both of these factors are recognised to impact upon swallow function 7,16 . For example, the slightly lower mean BMI in the prophylactic gastrostomy group may reflect a tendancy to choose this approach in patients who may be nutritionally compromised pre-treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The use of concurrent chemoradiotherapy is associated with clinically significant rates of severe long term dysphagia 16,17 . For example, an analysis of 3 RTOG studies found 13% of patients were gastrostomy-dependent 2 years post treatment 16 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The radiotherapy treatment for head and neck cancer can be frequently complicated by swallowing dysfunction, xerostomia, dysphonia, and soft tissue fibrosis, affecting the general dimension of quality of life [1][2][3]. To improve tumour local control with lower toxicities, a detailed accuracy in delineating target volumes and OARs is required.…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy treatment on head and neck regions is frequently complicated by late effects as swallowing dysfunction, dysphagia, and dysphonia [1,2]. The larynx is involved in complex mechanisms related to swallowing, respiration, and phonation and its irradiation can develop treatmentrelated sequelae [3][4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%